Measurement of the top-quark mass in tt̄ + 1-jet events collected with the ATLAS detector in pp collisions at √s = 8 TeV - Aaboud, Morad; Anders, Christoph; Andrei, George Victor; Antel, Claire; Bolz, Arthur; Brandt, Oleg; Dunford, Monica; Ferreira de Lima, Danilo Enoque; Franchino, Silvia; Geisler, Manuel Patrice; Helary, Louis; Jongmanns, Jan; et al. (Journal of high energy physics, 2019)
A determination of the top-quark mass is presented using 20.2 fb-1 of 8 TeV proton-proton collision data produced by the Large Hadron Collider and collected by the ATLAS experiment. The normalised differential cross section of top-quark pair production in association with an energetic jet is measured in the lepton+jets final state and unfolded to parton and particle levels. The unfolded distribution at parton level can be described using next-to-leading-order QCD predictions in terms of either the top-quark pole mass or the running mass as defined in the (modified) minimal subtraction scheme. A comparison between the experimental distribution and the theoretical prediction allows the top-quark mass to be extracted in the two schemes. The value obtained for the pole-mass scheme is: rnirle 171.1 0.4 (stat) 0.9 (syst) 173 (theo) GeV. The extracted value in the running-mass scheme is: rnt(rnt) = 162.9 0.5 (stat) 1.0 (syst) 1:12 (theo) GeV. The results for the top -quark mass using the two schemes are consistent, when translated from one scheme to the other.